Getting rid of Keynes? A survey of the history of macroeconomics from Keynes to Lucas and beyond - Michel De Vroey (National Bank of Belgium, 2010)
The aim of this paper is to recount the ebbs and flows of Keynesianism over the history of macroeconomics. The bulk of the paper consists of a discussion of the main episodes of the unfolding of macroeconomics (Keynesian macroeconomics, monetarism, new classical macroeconomics, real business cycle models and new neoclassical synthesis models) against the background of a distinction between Keynesianism as a `moderately conservative' (Keynes's words) vision about the working of the market system and as a conceptual apparatus. Particular attention is given to the contrast between Keynesian and Lucasian macroeconomics. The paper ends with a few remarks about the impact of the present crisis on the development of macroeconomic theory
Keywords: B22; 330; Keynes; Lucas; history of macroeconomics; Makroökonomik; Ökonomische Ideengeschichte; Keynesianismus; Neue klassische Makroökonomik